Sudden death in young athletes - Malina, R. M.
Over the past year and one-half, there have been three reports in the medical literature dealing with sudden death in young athletes. Two broad categories were described, (1) those due to trauma and (2) those not associated with trauma. The following is a brief overview of the conditions described in the three articles.